The Criminal Liability for Debtors Who Provides Fake Letter to Creditors to Get Credit Criminal Liability - Ni Made Trisna Dewi (Fakultas Hukum, Universitas Warmadewa, 2022)
The issue described in this study is about which letters can be an objects of falsified by debtors to get credit from creditor and how is the debtors accountability for providing fake letters to creditors. The method used in this research is normative, which is emphasizes the gap in norms that occur, this normative analysis mainly using library materials and laws and regulations as the source of research material. The results shows that there are several letters that can be falsified, such as: Letter of Assignment, ID, Family Card, Pay Slip. The purpose is to show that the letter seems to come from someone other than the author (perpetrator) so it is called material forgery (material valsheid), the origin of the letter is fake. Then, the act of falsifying a letter is carried out by making unauthorized changes (without the rightful permission) in a letter or writing, regarding the signature or the contents. Criminal liability for debtors who provide fake letters to creditors is leading to criminal prosecution of the perpetrators, if they have violated the provisions of Article 263 of the Criminal Code and fulfill the elements of Article 263 of the Criminal Code and the ability to be responsible is an element of error, therefore to prove the element of error, then the element of responsibility must also be proven, however, to prove the existence of an element of accountability is very difficult and requires time and money, so in practice it is used that everyone is considered capable of being responsible unless there are signs that indicate otherwise.